Status and Distribution of the Gangetic Dolphin, Platanista Gangetica Gangetica (Roxburgh, 1801) In River Buriganga During 2003-2004 and Its Conservation (Bangladesh Journal of Zoology, 2012)
Studies on the population status, distribution and conservation issues of the Gangetic dolphin Platanista gangetica gangetica were undertaken in the river Buriganga from November 2003 to November 2004. A total of 29 sightings with the highest of five sightings and a best-high-low estimate of 9-11-7 individuals were recorded in November 2004, while in the months of August and October no dolphin was observed. The mean density was 0.25 dolphin/km and the highest encounter rate was 0.29 sightings/km. Of the total sightings, 41.38% were in the groups of more than one individuals. Of the observed dolphins, 71.43% were adults,16.66% maturing and 11.9% young. The dolphins were found in 15 locations with both single as well as multiple sightings. Main threat to the dolphins was found to be pollution followed by traffic load and dredging activities. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12890 Bangladesh J. Zool. 40(1): 21-31, 2012